Floundering Stability US Foreign Policy in Egypt - Kamel, Amir Magdy (University of Michigan Press, 2023)
The US commitment to stability-both domestically and abroad-has been a consistent feature in the way Washington, DC carries out international relations. This commitment is complimented by the increased overlap between the economic and political spheres in international affairs. Consequently, this US approach to foreign interaction is informed by an assumption that foreign policy tools can influence global stability for the better. In order to investigate this assumption, this book details the foundations of what Amir Magdy Kamel refers to as the US Stability Policy-how it evolved over time and how it was implemented in Egypt. He finds that domestic and global forces were left unaccounted for by the Stability Policy, ultimately leading to a failure to achieve the self-stated stability goals. Kamel's analysis is informed through a unique mixed-method approach that sheds light on how and why this policy fared so poorly under Mubarak's Egypt. He develops and tests a unique and particular way of examining the Stability Policy and presents a framework for future work to replicate and build on in the quest to understand other state-on-state relationships and the effectiveness of other foreign economic policies in achieving stability goals. Floundering Stability reflects on what Kamel's findings mean for the relationship between the US and Egypt, as well as specific US foreign policy suggestions on how the same mistakes can be avoided in the future.